Structure and Substrate Recognition of the Bottromycin Maturation Enzyme BotP. (20th October 2016) - Mann, Greg; Huo, Liujie; Adam, Sebastian; Nardone, Brunello; Vendome, Jeremie; Westwood, Nicholas James; Müller, Rolf; Koehnke, Jesko
Abstract: The bottromycins are a family of highly modified peptide natural products, which display potent antimicrobial activity against Gram‐positive bacteria, including methicillin‐resistant Staphylococcus aureus . Bottromycins have recently been shown to be ribosomally synthesized and post‐translationally modified peptides (RiPPs). Unique amongst RiPPs, the precursor peptide BotA contains a C‐terminal "follower" sequence, rather than the canonical N‐terminal "leader" sequence. We report herein the structural and biochemical characterization of BotP, a leucyl‐aminopeptidase‐like enzyme from the bottromycin pathway. We demonstrate that BotP is responsible for the removal of the N‐terminal methionine from the precursor peptide. Determining the crystal structures of both apo BotP and BotP in complex with Mn 2+ allowed us to model a BotP/substrate complex and to rationalize substrate recognition. Our data represent the first step towards targeted compound modification to unlock the full antibiotic potential of bottro‐ mycin. Abstract : How does BotP do it? Understanding the biosynthesis of bottromycins will permit biotechnological engineering to unlock their pharmaceutical potential. The structural and biochemical studies of BotP, an essential maturation enzyme in the bottromycin synthetic pathway, are the first to be presented for the bottromycin biosynthetic enzymes.